Bonney's gynaecological surgery - Lopes, Tito.; Bonney, Victor, 1872-1953. (Chichester : Wiley-Blackwell, 2011)
Firm favourite for gynaecological surgical practice since 1911, extensively revised by leading gynaecological surgeons; Providing information on reconstructive surgery, anaesthesia, information technology and audit, complications and quality; Focusing on the most commonly performed procedures with emphasis on evidence-based decision making and the increasing use of laparoscopy in diagnostic and surgical procedures.
Bonney's Gynaecological Surgery; Contents; Preface to the eleventh edition; Preface to the ninth edition; Part 1: General; 1: Introduction and prologue; 2: Preparation for surgery; 3: Instruments, operative materials and basic surgical techniques; 4: Opening and closing the abdominal cavity; 5: The laparoscopic approach in gynaecology; 6: Postoperative care and complications; Part 2: Anatomical For the general gynaecologist and gynaecologist in training; 7: Operations on the vulva; 8: Operations on the vagina; 9: Operations on the cervix; 10: Operations on the uterine cavity.
Includes bibliographical references and index.
Print version record.
Keywords: Generative organs, Female -- Surgery; Gynecologic Surgical Procedures; Genitalia, Female -- surgery; Generative organs, Female; Surgery; Medicine; MEDICAL -- Reproductive Medicine & Technology; HEALTH & FITNESS -- Women's Health; Generative organs, Female -- Surgery; Electronic books